iPhone app and web service for ROSE (review & opinion search engine) - Pheng, Sovanlandy. (2012)
This FYP report describes the author's fruitful experience in the course of joining the sentiment analysis software developer team under the code name 'ROSE' (Review & Opinion Search Engine) as both the front-end and back-end developer. This report in general discusses and compares the choice of software/frameworks used, their alternatives and comparative analysis of each decision made, the problems face during the design and development phase, and their corresponding solutions.